Lifestyles of university students in Bosnia and Herzegovina (Journal of Health Sciences, 2017)
Introduction: Currently, there is a growing interest in alcoholism-related studies among healthcare community. Cigarette smoking is five times more prevalent among adult men compared to women but these gender differences have been decreasing among young people. In developed countries, harmful effects of sedentary lifestyle and physical inactivity have led to increased rates of obesity in young population. The main aim of this study was to explore the lifestyles of students at the University of Sarajevo. We investigated the prevalence of cigarette smoking and alcohol consumption, eating habits, and physical activity in this student population.Methods: Students from Faculty of Health Sciences [FHS], Faculty of Political Science [FPS], and Faculty of Traffic Engineering and Communications [FTEC]) voluntarily participated in this questionnaire-based study. We surveyed a total of 410 students.Results: On average, 21.8% of participants consumed cigarettes (a significantly higher number of those who smoked cigarettes was in FPS group). The highest number of students who reported physical activity (recreational or active sport) was in FTEC group (66.5%), and the difference was statistically significant compared to FHS (48.2%) and FPS (51.9%) groups. Over 60% of participants in all three groups experienced stress occasionally. The majority of students in three groups consumed fast food while at campus. The highest number of students in all three groups reported to drink water compared to other drinks.Conclusions: Our results indicate that the lifestyles of university students in Sarajevo are subject to concern. Frequent alcohol consumption and cigarette smoking are typical examples of behaviour that should be reduced through educative programs and workshops.